The binational survey in San Diego and Tijuana - Weeks, John R. (Frontera Norte, 2017)
The International Population Center at San Diego State University has collaborated with the Department of Population Studies at El Colegio de la Frontera Norte to conduct a pilot study for a larger project called The Demographic Interrelatedness of the U.S.-Mexico Border Project. The pilot study took place in late 1988 and early 1989 in the San Diego-Tijuana metropolitan region.